Assessment of PV modules shunt resistance dependence on solar irradiance. (August 2016) - Ruschel, Cristiano Saboia; Gasparin, Fabiano Perin; Costa, Eurides Ramos; Krenzinger, Arno
Highlights: I – V curves of photovoltaic modules of six technologies were measured on 20 irradiance levels. The shunt resistance parameter for each measurement was calculated. Fitting equations were obtained for each PV technology. The shunt resistance increased on lower irradiances. An inverse dependence of the shunt resistance on the irradiance described adequately the measured data. Abstract: Modeling and simulation of photovoltaic systems, further than aiding on the project design phase, can be used to emulate the system performance in real time, therefore helping to identify any malfunction that may occur. Among the available performance models for photovoltaic systems, the single diode model is preferred by many authors, since it combines relative simplicity and accuracy. Previous works reported that this model has some limitations on describing the photovoltaic system I – V curves under low irradiances, indicating that the variation of the shunt resistance parameter with the irradiance level can be adopted to minimize this drawback. This paper aims to study the shunt resistance dependence on the irradiance level in order to evaluate some of the usual expressions proposed on the literature. A large area pulsed solar simulator model PASAN SunSim 3C was used to acquire the I – V characteristics of several photovoltaic modules of different brands and technologies under 20 distinct irradiance levels ranging from 75 W/m 2 to 1000 W/m 2 . The shunt resistance parameter was calculated as the inverse slope of the I – V curve in the short circuit region, and fitting equations were derived for each photovoltaic technology. The results in general agreed with previous published works, showing the tendency of an increase of the shunt resistance on lower irradiance levels. Some empirical models tested did not present satisfactory accuracy to reproduce the experimental data. Although simpler, an inverse dependence of the shunt resistance on the irradiance using the measured value at STC as a reference was seen to describe adequately the experimental data. A preliminary study showed that the inclusion of this dependence on the single-diode model indeed increases the model accuracy, reducing the average error on the performed tests by more than half comparing to the original model.